DESIGNING SIGNAGE AND WAYFINDING AS INFORMATION FOR LAWANG SEWU - Noll, Patrecia Dwi Maharani; Ar Razi, Aria; Ayu, Intan Kusuma (eProceedings of Art & Design, 2024)
Historical Tourism in Indonesia is one of the things that is of interest to tourists. This is due to tourists' curiosity about history - history that occurred in the past. Then historical tourism is also important for visitors to increase their opinion of the surrounding area, and visitors can better appreciate the story behind it. One example is Lawang Sewu which is located in Semarang, Indonesia. This iconic structure, known as the "Thousand Doors", serves as a reminder of Indonesia's colonial past and its journey to independence. Built during the Dutch colonial period in the early 20th century, Lawang Sewu offers architectural charm that attracts visitors from all over the world. Lawang Sewu is also a witness to the history of the development of trains in Indonesia. The historical value of Lawang Sewu is the cornerstone of Semarang's tourism industry, attracting curious tourists who want to delve into the past. By preserving this architectural gem and highlighting its historical importance, Semarang can capitalize on its cultural tourism potential, encouraging economic growth and appreciation of Indonesia's diverse cultural heritage. This research aims to create interactive signage and wayfinding for visitors so that they can easily find out where they are, and don't forget to also provide the information needed by visitors.. The research method used to analyze and obtain the required data is a qualitative method supported by interviews with experts and also questionnaires distributed related to Lawang Sewu. This Interactive Signage is aimed at the audience who are visiting Lawang Sewu with a barcode in it so that they can get information about Lawang Sewu so that the audience can learn more. appreciate the story behind Lawang Sewu, and don't forget to preserve historical buildings in Indonesia. Keywords: signage and wayfinding, environmental graphic design, Lawang Sewu, historical tourism.